Colin Gunton and the Failure of Augustine : the theology of Colin Gunton in Light of Augustine - Green, Bradley G., 1965- (Cambridge, U.K. : James Clarke & Co., 2012)
Bradley G. Greens close reading of Augustine challenges Colin Guntons argument that Augustine bequeathed to the West a theological tradition with serious deficiencies. According to Gunton, Augustines particular construal of the doctrine of God led to fundamental problems in the relationship between creation and redemption. However, Green persuasively argues that Augustine did not sever the link between creation and redemption, but rather affirmed that the created order is a means of genuine knowledge of God by which redemption is accomplished. Green suggests the prominent role this relationshi.
Augustine and AristotleBeing of God as a Model; Persons, Substance, and Ontology; Conclusion; Chapter Six; The One and the Many; Creation; Creation and God's Will; Creation and Trinity; Creation and Revelation; The Order and Purpose of Creation; Redemption; Missions and Processions; Te Centrality of the Incarnation and the Cross; Te Holy Spirit and God's Relationship to the World; Ontology; Te One and the Tree; Tree Persons, One God; Being and Relationship; Te Trinity, the Imago Dei, and Being; Conclusion; Chapter Seven; Augustine and Gunton; Possibilities for Further Research; Bibliography.
Includes bibliographical references (pages 207-219).
Master record variable field(s) change: 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Gunton, Colin E; Augustine, -- Saint, Bishop of Hippo; Gunton, Colin E; Augustine, -- Saint, Bishop of Hippo; Gunton, Colin E; Theology; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; RELIGION -- Christian Theology -- History; Theology; Electronic books